2022
DOI: 10.1093/sleep/zsac079.270
|View full text |Cite
|
Sign up to set email alerts
|

0272 Decreased Risk of 2-Year Incidence of Alzheimer’s Disease Among Older Adults Who Report Sleep Symptoms

Abstract: Introduction Those with dementia or Alzheimer’s Disease report an elevated amount of sleep difficulties compared to age-matched controls. Sleep-based interventions may be especially useful for this group, such as cognitive behavioral therapy for insomnia or pharmacological interventions. Therefore, it is important to expand the current understanding of the nature of sleep difficulties in those with Alzheimer’s Disease. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Despite the initial hypotheses, though, respondents with sleep-maintenance insomnia were less likely to develop dementia over the course of the decade than respondents who did not report insomnia. This negative association falls in an interesting spot in the literature: while some studies have found positive associations, 11,22 others have similarly found negative ones 23 or no association at all. 21,24 These mixed results deserve further research for their own clarity, but, if the negative association is correct, more investigation should be done on how these conditions can connect counterintuitively.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Despite the initial hypotheses, though, respondents with sleep-maintenance insomnia were less likely to develop dementia over the course of the decade than respondents who did not report insomnia. This negative association falls in an interesting spot in the literature: while some studies have found positive associations, 11,22 others have similarly found negative ones 23 or no association at all. 21,24 These mixed results deserve further research for their own clarity, but, if the negative association is correct, more investigation should be done on how these conditions can connect counterintuitively.…”
Section: Discussionmentioning
confidence: 84%
“…25 This extra productivity may be the mechanism by which those with sleep-maintenance insomnia reduce their own dementia risk over the years. 23 Lastly, sleep medication usage was significantly associated with dementia incidence in only the second of the Cox regression models. This finding was partially expected: many older adults take sleep medication due to their health conditions, 27 and controlling for health variables would have thus attenuated the association between sleep medication and dementia.…”
Section: Discussionmentioning
confidence: 97%